2005
DOI: 10.1161/01.str.0000177878.33559.fe
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Tumor Necrosis Factor-α in Skeletal Muscle After Stroke

Abstract: Background and Purpose-Tumor necrosis factor-␣ (TNF-␣), an inflammatory cytokine negligibly expressed in normal muscle, is elevated in selected metabolic conditions characterized by muscle wasting and insulin resistance. Inflammation is fundamental to stroke pathogenesis. Stroke patients have gross muscular atrophy and high prevalence of diabetes and insulin resistance. Yet, no previous studies examined TNF-␣ expression in hemiparetic skeletal muscle. This study investigates whether TNF-␣ mRNA levels are eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 16 publications
2
65
0
Order By: Relevance
“…We previously reported that TNF-α levels were significantly elevated in the VL muscles of the paretic compared with the nonparetic leg after stroke [14]. In the present study, we report elevated gene expression of a disintegrin and metalloprotease (ADAM) in the paretic leg muscle after stroke.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…We previously reported that TNF-α levels were significantly elevated in the VL muscles of the paretic compared with the nonparetic leg after stroke [14]. In the present study, we report elevated gene expression of a disintegrin and metalloprotease (ADAM) in the paretic leg muscle after stroke.…”
Section: Discussionsupporting
confidence: 55%
“…The loss of slow-twitch fibers that take up glucose in response to insulin is relevant to the high prevalence of insulin resistance in stroke survivors [13]. In addition, expression of tumor necrosis factor alpha (TNF-α), an inflammatory cytokine, is elevated in the hemiparetic leg muscle compared with the nonparetic leg muscle [14]. Whether broader inflammatory pathway activation is present with subsequent downstream impact on muscle cell cycle, protein synthesis, or metabolic function is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…58,59 It has been shown that elevated volumes of TNF-α are responsible for muscle loss and that plasma concentrations of the enzyme visfatin were significantly elevated in patients after ischemic stroke. 60,61 For that, investigations to changes of inflammation parameters and its relation to body composition, insulin sensitivity, and patient's survival will be made as well. 55 …”
Section: Current Developments On Muscle Mass Lossmentioning
confidence: 99%
“…Specifically, a deficit severity-dependent shift toward a fast-twitch muscle molecular phenotype in the paretic leg results in a more fatigable muscle fiber type that is more insulin resistant, which may contribute to the high incidence of IGT in this population [31][32][33]. Furthermore, nearly threefold elevated levels of tumor necrosis factor-α (TNF-α) messenger RNA are reported in hemiparetic quadriceps muscle from patients with stroke compared with those from nonparetic legs and nonstroke control subjects [34]. Elevated TNF-α levels in skeletal muscle tissue are strongly linked to muscular wasting and insulin resistance in T2DM and advancing age and may contribute to the structural and metabolic abnormalities in hemiparetic skeletal muscle after stroke [35][36][37][38].…”
Section: Tissue-level Abnormalities After Strokementioning
confidence: 99%